J23 Coach–athlete relationship as a predictor of contextual motivation in weightlifters - Mehta, Jinal S (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Coach behaviour is an important predictor of athlete motivation (Jowett, 2017). The coach–athlete relationship can be defined as a dynamic interaction wherein the feelings, thoughts and behaviours of both athlete and coaches are mutually and causally interconnected (Jowett and Shanmugam, 2016, In Schinke, McGannon & Smith (Eds.), Routledge International Handbook of Sport Psychology, Relational Coaching in Sport: Its psychological underpinnings and practical effectiveness (pp. 471–484). Routledge). This present study explored the coach–athlete relationship through the lens of Self-Determination Theory. This multidimensional theory underscores various facets of motivation suggesting that coaches’ behaviours influence athletes’ motivation by directly influencing their three basic psychological needs (Deci & Ryan, 2008, Can Psych, 49, 182–185). The study builds on previous research highlighting the pivotal role of coaches in shaping positive sporting environments and the significance of closeness, commitment and compatibility in the coach–athlete relationship (Jowett & Nezlek, 2012, J Soc Pers Rel, 29, 287–301). The purpose of the present study was to further understanding of the association between the coach–athlete relationship and contextual motivation among weightlifters. Previous studies have expounded a motivational model of the coach–athlete relationship that outlined a sequence wherein coaches’ actions bear influence on athletes’ intrinsic and self-determined extrinsic motivation by shaping their perceptions of autonomy, competence, and relatedness (Mageau & Vallerand, 2003, J Sports Sci, 21, 883–904). It was hypothesised that a coach–athlete relationship scores would be a negative predictor of amotivation and external regulation (H1). It would, however, be a positive predictor of more intrinsic forms of motivation (H2). Specifically, those who perceive their coaches as supportive, understanding and competent will report higher levels of intrinsic motivation within the training environment. Following institutional ethical clearance (33249-A-Nov/2023-47988-1), a sample of male and female weightlifters (N = 20; females = 11) were asked to complete an 11-item version of Coach–Athlete Relationship Questionnaire (CART-Q; Jowett & Ntoumanis, 2003) and the 18-item Sports Motivation Scale (SMS-2; Pelletier et al., 2013). There was no time gap in the administration of the two questionnaires. A series of standard linear regression analyses was computed using CART-Q subscales as predictor variables and each SMS-2 subscale as the dependent variable. H1 was not supported, as the CART-Q subscales were not a significant negative predictor of amotivation and external forms of motivation. H2 was supported given that the CART-Q subscales were positive predictors of intrinsic motivation subscales.